EFFECTIVENESS OF USING NON-TRADITIONAL TECHNOLOGIES FOR SLEEP DISORDERS - Мальцева, Ольга (SWorldJournal, 2025)
The article is devoted to the problem of stress resistance of students, that suffer from cases of sleep disorders, during the session. Young people, faced with new methods of studying at universities that differ from school, do not always cope with the re